(untitled) (Journal of Veterinary Medicine and Animal Production, 2022)
A one year old female Saanen goat(Capra aegagrus hircus) was admitted to the Veterinary Teaching Hospital of The University of Khartoum representing a sample of a small herd that was housed by a smallholder in Omdurman Locality in Khartoum State. The main clinical manifestations were different sizes of rounded raised scaling skin lesions with scabs on their tops and painul on palpation. Lesions were spread all over the body, especially on the ears, eyelids and under the base of the tail. The case was tentatively diagnosed as dermatophytosis. Skin scrapings were collected for mycological studies. Direct mounts of the scrapings were performed in 20% KOH. Cultures onto brain heart infusion agar and sub-cultures onto Sabouraud Dextrose Agar were performed . Confirmation mounts from colonies have been done. In lactophenol cotton blue Trichophyton verrucosum has been isolated.